French Beliefs: Walter Pater and Contemporary French Fiction - Bénédicte Coste (Cahiers Victoriens et Edouardiens)
This article discusses Walter Pater’s reviews of contemporary French writings in British periodicals between 1886 and 1890 to show that the choice of periodicals, reviewed writings (novels, correspondence) obeys social and journalistic constraints of the mid to late 1880s when debates on morality and media campaigns mostly targeted avant-garde French literature and writers like Zola and Flaubert. However Pater proved adroit in reviewing both controversial writers and recognized authors such as Feuillet, Lemaître, Filon, Fabre, Amiel, subtly pitting both camps to make his own opinions more indefinite but more importantly considering the question of belief since all texts and authors discussed are notable for their confronting the question of belief. Pater’s skilful negotiation of cultural and journalistic constraints enabled the reviewer to present his own conception of belief.